2022
DOI: 10.3389/fpls.2022.1019831
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chloroplast genome analyses of Paraboea (Gesneriaceae): Insights into adaptive evolution and phylogenetic analysis

Abstract: Paraboea (Gesneriaceae) distributed in the karst areas of South and Southwest China and Southeast Asia, is an ideal genus to study the phylogeny and adaptive evolution of karst plants. In this study, the complete chloroplast genomes of twelve Paraboea species were sequenced and analyzed. Twelve chloroplast genomes ranged in size from 153166 to 154245 bp. Each chloroplast genome had a typical quartile structure, and relatively conserved type and number of gene components, including 131 genes which are composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…A previous study also reported the loss of the trnH -GUG genes was one of the major differences between the plastomes of the two subgenera Siphisia and Aristolochia ( Li et al., 2019 ). These sequence variations might be the result of boundary contraction and expansion between the LSC/IR regions in plants ( Wang et al., 2022 ). Plastid genomes have the characteristics of high conservation and slow evolutionary rate, thus the special characteristics presented in their structure are often phylogenetically informative ( Pascual-Diaz et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also reported the loss of the trnH -GUG genes was one of the major differences between the plastomes of the two subgenera Siphisia and Aristolochia ( Li et al., 2019 ). These sequence variations might be the result of boundary contraction and expansion between the LSC/IR regions in plants ( Wang et al., 2022 ). Plastid genomes have the characteristics of high conservation and slow evolutionary rate, thus the special characteristics presented in their structure are often phylogenetically informative ( Pascual-Diaz et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high conservatism of plastome has also been observed in other Gesneriaceae genera. For instance, Wang et al. (2022) found that the plastomes length of Paraboea ranged from 153,166–154,245 bp and exhibited similar structure, gene order, and gene content.…”
Section: Discussionmentioning
confidence: 99%
“…The chloroplast genome sequences were used to study systematic evolutionary relationships between species of Swertia L. It was found that rpoC1, ccsA, ndhI, ndhA, and rps15 protein-coding genes had large variations [21]. The complete chloroplast genomes of Paraboea (Gesneriaceae) plants were used to study their phylogeny and adaptive evolution [22]. The complete chloroplast genomes of Ipomoea were used to construct a phylogenetic tree in our study.…”
Section: Organellar Phylogenetic Relationshipmentioning
confidence: 99%